Regions and regional planning in Turkey - Karakayacı, Özer (Regiony i planowanie regionalne w Turcji, 2015)
Region is evaluated as a spatial unit which defines the economic-social structure and in which the planning processes like determining, implementing, managing and inspecting the regional development strategies and politics changing within the scope of paradigm changes are carried out. In Turkey, experience related to regional development politics goes back to the 1960s; it has been analysed to what extent regional planning and the concept of a region are affected by the changing processes which are experienced in economic and social structure, according to which criteria the borders for regional planning are determined and the role of these borders in the success of regional politics. According to the results, being unable to provide the interaction between regional planning and the meaning attributed to the concept of a region is the main factor in the non-occurrence of the success which has been aimed in regional development politics although regional planning and the concepts of a region are affected from the paradigm changes
Biblioteka Regionalisty, 2015, Nr 15, s. 33-46
Keywords: Turkey; regional planning; regions; Turcja; planowanie regionalne; regiony